Burnout, physical activity and professional experience in Icelandic elementary school teachers - Ásgerður María Rivina 1996- (2019)
Burnout is a recognized occupational disorder most often defined as a physical and psychological consequence of prolonged exposure to stressors in an individual’s work environment. Teaching is considered to be a stressful profession and incidence of burnout has been reported in the educational profession. The current research study aimed to examine burnout in Icelandic elementary school teachers and whether there was a connection between burnout, professional experience, and physical activity. Participants in the current research study were 43 elementary school teachers out of three schools in Iceland which completed a self-report questionnaire. The participants were born from 1950 to1989, and of them, 37 were female (86%), and 6 were male (14%). The results revealed that in the current sample of an elementary school teacher the frequency of pronounced burnout and moderate/mild burnout was 41.9%. A significant negative connection was found between burnout and physical activity. Teachers that engaged in more physical activity per week (80%) were significantly more likely to have no burnout than teachers that engaged less frequently in physical activity (39.1%). No significant connection between professional experience and symptoms of burnout was found which requires further investigation. Future research should address that issue and focus on which types and intensity of physical activity are most suitable to prevent burnout. Also, more longitude studies are needed to research burnout in teachers. Keywords: Teachers’ Burnout, Work Related Stress, Professional Experience, Physical Activity Kulnun er viðurkennd streitutengd röskun sem oftast er skilgreind sem líffræðileg og sálfræðileg svörun við langvarandi streitu sem kemur í kjölfar upplifunar á streituvöldum í vinnuumhverfi fólks. Kennsla er talin vera streituvaldandi starfsgrein og greint hefur verið frá tíðni kulnunar í kennarastarfinu. Markmið með þessari rannsókn var að skoða kulnun íslenskra grunnskólakennara og hvort að líkamleg hreyfing og starfsaldur ...